Visual representation of strength and masculinity in male supplement product packaging - Hartono, Hendri; Margaretha, Regyna; Afrilia, Nur Sitha (Priviet Social Sciences Journal, 2026)
This study critically investigates the visual strategies employed in the packaging of male supplement products in Indonesia, emphasizing how prevailing design practices frequently prioritize erotic imagery and hyper-masculine aesthetics over educational and ethical communication. Utilizing a qualitative descriptive method grounded in semiotic analysis and visual communication design (VCD) theory, this research examines selected product packaging through the lenses of color, typography, composition, and imagery. The findings show a tendency to sexualize visual elements, like exaggerated male symbols, overtly sexualized depictions of women, and overly aggressive color schemes. This reduces health products to sexual commodities. These strategies not only disregard local cultural values but also obfuscate crucial medical information, including dosage, ingredients, and potential side effects, thereby undermining consumer health literacy. A critical evaluation of the subject packaging reveals its contribution to the perpetuation of patriarchal gender norms and reinforcement of toxic masculinity. Furthermore, there is a failure on the part of the packaging to adequately address the professional responsibilities inherent to health communication. This phenomenon reflects a systemic failure within the industry to understand design ethics and cultural representation. The study calls upon producers to transition from superficial marketing tactics to more reflective and responsible design strategies. Integral to this approach is the fostering of interdisciplinary collaboration among designers, experts in gender studies, and cultural scholars with the objective of developing packaging that respects social values while conveying accurate information and building long-term brand credibility. It is imperative to reposition packaging as a medium of education and ethical representation to transform the male supplement market into a space that supports both health and dignity.